Personalised functional imaging-guided multitarget continuous theta burst stimulation for post-stroke aphasia: study protocol for a randomised controlled trial - Wuxiang Xie; Na Xu; Hesheng Liu; Jianting Huang; Jianxun Ren; Ruiqi Pan (BMJ Open)
Introduction Continuous theta burst stimulation (cTBS), a form of repetitive transcranial magnetic stimulation (rTMS), targeting the language network in the right hemisphere of post-stroke aphasia (PSA) patients shows promising results in clinical trials. However, existing PSA studies have focused on single-target rTMS, leaving unexplored the potential benefits of multitarget brain stimulation. Consequently, there is a need for a randomised clinical trial aimed to evaluate the efficacy and safety of cTBS targeting on multiple critical nodes in the language network for PSA.Methods and analysis This is a prospective, multicentre, double-blind, two-arm parallel-group, sham-controlled randomised trial. The study will include a total of 60 participants who will be randomly assigned in a 1:1 ratio to either the active cTBS group or the sham cTBS group. Using precision resting-state functional MRI for each participant, we will map personalised language networks and design personalised targets in the inferior frontal gyrus, superior temporal gyrus and superior frontal gyrus. Participants will undergo a 3-week cTBS intervention targeting the three personalised targets, coupled with speech and language therapy. The primary outcome is the change in the Western Aphasia Battery-Revised aphasia quotient score among participants after a 3-week treatment. Secondary outcomes include Boston Diagnostic Aphasia Examination severity ratings, Token Test and the Chinese-version of the Stroke and Aphasia Quality of Life Scale 39-generic version.Ethics and dissemination The study has been approved by the ethics committees of Affiliated Hospital of Hebei University, Hebei General Hospital and Affiliated Hospital of Chengde Medical University. The findings of this study will be reported in peer-reviewed scientific journals.Trial registration number The study has been registered on ClinicalTrials.gov (NCT05957445).